2020
DOI: 10.1155/2020/2315230
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Alleviated High-Fat-Diet-Induced Hepatocytic Apoptosis via Peroxisome Proliferator-Activated Receptor γ

Abstract: Objective. High-fat-diet- (HFD-) induced hepatic cell apoptosis is common in mice with nonalcoholic fatty liver disease (NAFLD). We aim to investigate the effect of Ginsenoside Rb1 (GRb1) on hepatocyte apoptosis. Methods. C57BL/6J mice with HFD were used to induce a liver-injured model with cell apoptosis. In addition, GRb1 was used to treat HFD-induced apoptosis in a liver with or without inhibitor of peroxisome proliferator-activated receptor γ (PPAR-γ). Results. Compared with C57BL/6J mice with common chow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Rb1 can decrease body weight, increase insulin sensitivity, suppress liver fat accumulation, regulate adipocyte function and improve glucose tolerance in obese mice and rats ( Xiong et al, 2010 ; Shen et al, 2013 , 2015 ; Lin et al, 2014 ; Yu et al, 2015 ; Song et al, 2017 ; Lim et al, 2019 ). Rb1 exerts multi-target effects and its molecular mechanism mainly involves in activating AMP-activated protein kinase ( Shen et al, 2013 ; Zhao et al, 2019 ) and regulating PPARγ signaling ( Mu et al, 2015 ; Song et al, 2020 ). However, these pharmacological effects were observed in the treatment via intraperitoneal injection of Rb1, and the molecular targets analyzed were mainly in the liver, skeletal muscle and adipose tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Rb1 can decrease body weight, increase insulin sensitivity, suppress liver fat accumulation, regulate adipocyte function and improve glucose tolerance in obese mice and rats ( Xiong et al, 2010 ; Shen et al, 2013 , 2015 ; Lin et al, 2014 ; Yu et al, 2015 ; Song et al, 2017 ; Lim et al, 2019 ). Rb1 exerts multi-target effects and its molecular mechanism mainly involves in activating AMP-activated protein kinase ( Shen et al, 2013 ; Zhao et al, 2019 ) and regulating PPARγ signaling ( Mu et al, 2015 ; Song et al, 2020 ). However, these pharmacological effects were observed in the treatment via intraperitoneal injection of Rb1, and the molecular targets analyzed were mainly in the liver, skeletal muscle and adipose tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have reported that some pure compounds or plant extracts may improve NAFLD [ 49 , 50 , 51 ]. Rutin could suppress hepatic lipid levels and oxidative injury to improve NAFLD in mice [ 52 ], ginsenoside Rg1 could effectively ameliorate hepatic steatosis and inflammation possibly via the AMPK/NF-kB pathway [ 53 ], and ginsenoside Rb1 alleviated high-fat diet-induced hepatocyte apoptosis in mice [ 54 ]. Red ginseng has been used as a natural medicine for various diseases in Asian countries for many years.…”
Section: Discussionmentioning
confidence: 99%
“… 44 GRb1 alleviates hepatocytic apoptosis via peroxisome proliferator-activated receptor γ. 45 Catalpol improves the mitochondrial membrane potential and regulates inflammatory cytokines and the expression of apoptotic proteins through antioxidant effects and protects the liver from cholestasis-mediated injury. 46 GA inhibits lipid accumulation, apoptosis and inflammation in hepatocytes by activating AMPK.…”
Section: Discussionmentioning
confidence: 99%